2012
DOI: 10.3390/genes3040686
|View full text |Cite
|
Sign up to set email alerts
|

Using Multiple Phenotype Assays and Epistasis Testing to Enhance the Reliability of RNAi Screening and Identify Regulators of Muscle Protein Degradation

Abstract: RNAi is a convenient, widely used tool for screening for genes of interest. We have recently used this technology to screen roughly 750 candidate genes, in C. elegans, for potential roles in regulating muscle protein degradation in vivo. To maximize confidence and assess reproducibility, we have only used previously validated RNAi constructs and have included time courses and replicates. To maximize mechanistic understanding, we have examined multiple sub-cellular phenotypes in multiple compartments in muscle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…This analysis revealed that 84% of the behavioral phenotypes observed in the present RNAi screen were consistent with past studies, whereas 7% of our observations appear to be the first report of a behavioral phenotype for knockdown of the targeted gene and 10% of our observations do not confirm past reports. These values are similar to other large-scale RNAi screens from our laboratory ( 18 , 28 ) and suggest that the level of variability in RNAi knockdown is roughly 10%, on par with many standard techniques such as Western blotting ( 29 ).…”
Section: Methodssupporting
confidence: 83%
“…This analysis revealed that 84% of the behavioral phenotypes observed in the present RNAi screen were consistent with past studies, whereas 7% of our observations appear to be the first report of a behavioral phenotype for knockdown of the targeted gene and 10% of our observations do not confirm past reports. These values are similar to other large-scale RNAi screens from our laboratory ( 18 , 28 ) and suggest that the level of variability in RNAi knockdown is roughly 10%, on par with many standard techniques such as Western blotting ( 29 ).…”
Section: Methodssupporting
confidence: 83%
“…If the clones we have identified are true positives, then these 155 clones should also have been retained. This gives a measure of the efficiency of the screen (360/(360 + 155), 70 %); in common with other RNAi screens (e.g., [ 32 , 33 ]), false negatives are thus a notable limitation here. Among the identified targets, in addition to rack-1 , we noted the presence of nipi-3 , nsy-1 , pkc-3 , sta-2 and tir-1 , all previously characterized for their role in regulating antimicrobial peptide gene expression [ 1 , 3 , 7 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, while our use of RNAi by feeding has allowed us to define a preliminary in vivo functional kinome requirement for muscle, our use of this single method will almost certainly have caused us to overlook certain kinases. For example, RNAi by feeding does not produce a reproducible quantitative knockdown from animal to animal [ 42 , 43 ]. Thus, negative results and quantitative differences in defects in response to RNAi against different genes are not interpretable, as it is experimentally challenging to demonstrate quantitative knockdown in the same worm that is scored for subcellular defects and economically not feasible on the scale of the work reported here.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi using bacterial clones grown as described [ 6 ] was performed with both chronic and acute RNAi experiments as described previously [ 12 ]. A detailed technical description of the strengths, limitations, and caveats to interpretation of results from this screening methodology is available elsewhere [ 43 ].…”
Section: Methodsmentioning
confidence: 99%